SHAKE-PROOF ONE-CHANNEL INTERFEROMETER - A. I. Konoiko; R. G. Sedniou; A. M. Polikanin (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
A method of transmission light beams based on birefringent elements and polarization transformations which eliminates the effect of destabilizing factors due to the fact that the interferometer is proposed to support and probing light beams pass through the same optical elements is proposed.